Hubungan Pola Asuh Orang Tua dengan Kedisiplinan Anak Kelompok Bermain di KB PAUD Anisa - Mita Sari; Siti Fadila; Sri Lestari Zainuddin; Nur Cynthia Roman; Novita Karim; Marsha S. Daud; Salwa Nevara Yusuf; Sri Nabila Hengkeng; Safira Nur Podungge; Nurfazria Y. Kaharu (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to determine the relationship between parenting styles and children's discipline in playgroups at the Anisa Early Childhood Education Center (KB PAUD). The research background is based on the important role of parents in shaping children's discipline from an early age. This study used a quantitative method with a correlational approach. The study population was all 40 parents and children in playgroups at the Anisa Early Childhood Education Center (KB PAUD). Data were collected through a questionnaire using a Likert scale, then analyzed using the Pearson Product Moment correlation test. The results showed that parenting styles were classified as high, with the majority of parents implementing a democratic parenting style characterized by open communication and consistent discipline. Children's discipline levels were also classified as high. The correlation test obtained an r value of 0.724 with a significance level of 0.000 (p < 0.05), indicating a positive and significant relationship between parenting styles and children's discipline. Therefore, the better the parenting styles implemented by parents, the higher the children's discipline levels.